Public Perception of Local Dialects and Its Implications for Cultural Identity - Aisyah Aulia Putri (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This study investigates the public perception of local dialects and their implications for cultural identity. Local dialects serve as vital markers of regional identity and heritage, yet they often face stigma and marginalization in favor of standardized languages. Through a mixed-methods approach, including surveys and in-depth interviews, the research examines how individuals perceive various local dialects in terms of prestige, authenticity, and social value. The findings reveal a nuanced landscape of attitudes, where some respondents express pride in their local dialects as symbols of cultural heritage, while others associate them with negative stereotypes, which impacts their willingness to use these dialects in public settings. The study highlights the complex relationship between language, identity, and social dynamics, suggesting that fostering positive perceptions of local dialects can enhance cultural pride and community cohesion. Additionally, the research discusses the role of education and media in shaping perceptions of local dialects and emphasizes the need for initiatives that promote linguistic diversity. Ultimately, this research underscores the importance of recognizing and valuing linguistic diversity as a crucial component of cultural identity in an increasingly globalized world, advocating for the preservation and celebration of local dialects to strengthen community ties and cultural heritage.